Development of an Age-Appropriate Mini Orally Disintegrating Carvedilol Tablet with Paediatric Biopharmaceutical Considerations - Dilawar Khan; Daniel Kirby; Simon Bryson; Maryam Shah; Afzal Rahman Mohammed (MDPI AG, 2021)
Owing to considerable differences observed in anatomy and physiology between paediatric subsets, it has been well established that children respond to drugs differently compared to adults. Furthermore, from a formulation perspective, there is a distinct challenge to develop a dosage form that is capable of safely, accurately, and reliably delivering the dose across the whole paediatric population. Orally disintegrating mini-tablets (ODMT) have widely been considered as an age-appropriate formulation option that possess the ability for adequate dose flexibility, avoids swallowing difficulties, and exhibits superior stability due to its solid state. Within this study, two strengths (0.5 mg and 2 mg) of carvedilol ODMT formulations were developed using an excipient composition and load that is appropriate for paediatric use. The formulations demonstrated adequate mechanical strength (>20 N) and fast disintegration times (<30 s). Dissolution profiles observed were robust and comparable to the marketed conventional tablet formulation across various parts of the gastrointestinal (GI) tract in both the fed and fasted state, signifying appropriate efficacy, quality, and performance. As such, the formulations developed in this study show potential to address the need of an 'age-appropriate' formulation of carvedilol, as highlighted by the European Medicines Agency (EMA) Inventory of the Needs for Paediatric Medicine.